2022
DOI: 10.1007/s11910-022-01231-5
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Ruin: Rehabilitation, Recovery, and Restoration After Stroke

Abstract: Purpose of Review Stroke is a common cause of disability in aging adults. A given individual’s needs after stroke vary as a function of the stroke extent and location. The purpose of this review was to discuss recent clinical investigations addressing rehabilitation of an array of overlapping functional domains. Recent Findings Research is ongoing in the domains of movement, cognition, attention, speech, language, swallowing, and mental health. To best assist patients’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 155 publications
(172 reference statements)
0
2
0
Order By: Relevance
“…Our study provides evidence that patients with aphasia, as a group, demonstrated improvement in speech rate, auditory comprehension and naming abilities. This is consistent with previous reports which indicate that usually the majority of people with aphasia following left hemisphere stroke perform better in language tasks within the first three to six months with little change thereafter [60].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study provides evidence that patients with aphasia, as a group, demonstrated improvement in speech rate, auditory comprehension and naming abilities. This is consistent with previous reports which indicate that usually the majority of people with aphasia following left hemisphere stroke perform better in language tasks within the first three to six months with little change thereafter [60].…”
Section: Discussionsupporting
confidence: 93%
“…One line of research also suggests that older individuals may possess greater cognitive resources that facilitate recovery, while younger individuals, despite the fact that they exhibit a greater degree of neuroplasticity, may face more important pathophysiological challenges related to the severity of stroke [15]. Our findings align with recent research which highlights that age and educational level are complex variables that encapsulate other important constructs in determining recovery outcomes [60]. For example, cognitive reserve, pre-existing language abilities or learning disabilities, socio-economic status and cultural influences may be pivotal in the language recovery even of two patients of the same chronological age.…”
Section: Discussionsupporting
confidence: 86%
“…Post-stroke dysarthria often presents comorbid with other speech and/or swallow impairments, such as dysphonia and dysphagia, as well as with cognitive deficits and motor impairments. Treatment of dysarthria and other communication impairments traditionally focus on behavioural interventions, but an estimated 100 speech language therapy hours are estimated for functional improvement [54]. Instead, combinatorial approaches including those that can be supervised remotely or be performed independently may increase success rate and improve outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a cerebral blood circulation disorder that may further induce neurological deficit, which is one of the main causes of disability and death in the global population ( 1 , 2 ). In addition, post-stroke mental disorders including anxiety, depression, and cognitive impairment have become an important clinical concern ( 1 , 3 , 4 ), negatively affecting the quality of life and disease rehabilitation in stroke patients ( 5 , 6 ). Through the deep understanding of the pathogenesis of these mental disorders, the role of immune dysfunctions driven by cluster of differentiation 4 + (CD4 + ) T cells in promoting the development of mental and cognitive problems has been recognized gradually ( 7 - 9 ).…”
Section: Introductionmentioning
confidence: 99%